2022
DOI: 10.1177/19417381221111395
|View full text |Cite
|
Sign up to set email alerts
|

Mask Use for Athletes: A Systematic Review of Safety and Performance Outcomes

Abstract: Context: With the current Centers for Disease Control and Prevention recommendations for mask use to minimize transmission of coronavirus 2019 (COVID-19) coupled with concern for future pandemics that would require mask wearing, providing data-driven guidance with respect to athletic performance is essential. Objective: The purpose of this study was to perform a systematic review of existing literature on the use of face masks while exercising to assess the physiologic effects of face masks worn during athleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the same direction, Amput and Wongphon [ 21 ] found that wearing cloth masks and surgical masks had no effect on cardiorespiratory parameters, such as HR, blood pressure, and SpO 2 at rest and after performing the 6-minute walk test. Moreover, the result of a systematic review by Lott et al [ 22 ] showed that wearing a mask in healthy individuals had no significant impact on the measured physiological parameters, including HR, respiratory rate, and SpO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the same direction, Amput and Wongphon [ 21 ] found that wearing cloth masks and surgical masks had no effect on cardiorespiratory parameters, such as HR, blood pressure, and SpO 2 at rest and after performing the 6-minute walk test. Moreover, the result of a systematic review by Lott et al [ 22 ] showed that wearing a mask in healthy individuals had no significant impact on the measured physiological parameters, including HR, respiratory rate, and SpO 2 .…”
Section: Discussionmentioning
confidence: 99%